Pengaruh Substitusi Tepung Mocaf dan Penambahan Puree Wortel terhadap Tingkat Kesukaan Kue Kuping Gajah - Okky Ayunda Uliawati; Lilis Sulandari; Lucia Tri Pangesthi; Asrul Bahar (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this study was to determine: 1) the effect of mocaf flour substitution on the level of likeability of elephant ear cake; 2) the effect of addition of carrot puree on the level of likeability of elephant ear cake; 3) the effect of the interaction between mocaf flour substitution and the addition of carrot puree on the level of likeability of elephant ear cake; and 4) the nutritional value of the best elephant ear cake product based on the results of chemical tests. This study is an experimental research type with a 3 x 2 factorial design with 6 treatments. The data collection technique in this study was in the form of observations carried out by 3 trained panelists, 31 semi-trained panelists, and 19 untrained panelists with data collection instruments using a hedonic test assessment sheet with criteria for color, aroma, crispiness, taste, and overall. The data analysis technique used was two-way ANOVA assisted by SPSS version 22 software and continued with Duncan's follow-up test if a significant interaction was found. The results showed that 1) mocaf flour substitution affected on the level of likeability of elephant ear cake in terms of crispiness and taste; 2) the addition of carrot puree did not have a significant effect on all aspects of preference; 3) the interaction between the two only affected the crispiness; and 4) the best nutritional content of elephant ear cake was obtained from 4.81% fat, 1.25% ash, 7.88% protein, 1.02% water, 82.01% carbohydrate, 2.82% fiber, and 86.50 mg/100g beta-carotene